Estimation of probiotic and vitamine D efficiency in prophylactics of infectious diseases in premature infants - Aryaev, N. L.; Shevchenko, I. M.; Moskalenko, T. Ya.; El Mezevgi, J. M.; Shevchenko, N. V. (Journal of Education, Health and Sport, 2017)
The objective: to study the efficacy of probiotic and vitamin D use in prophylaxis of infectious diseases in premature infants. Materials and methods. The reseach has been conducted on the base of theOdessaNationalMedicalUniversity– neonatal unit of the maternity hospital N 7 (Odessa). The I group consisted of 20 premature infants (PI) who got BioGiy drops. The II group conssted of 19 PI, who got BioGiy drops and vitamin D3. Control group- 23 PI who did not get the preparations mentioned above. At birth and at the age of 3-4 months complex immunological investigation was carried out. Every month the morbidity of PI was observed. Results. PI are more likely to suffer from infectious diseases, functional disorders of the gastrointestinal tract and hypovitaminosis D. The results obtained indicate a high effectiveness of probiotic with vitamin D3 use for the prevention of infectious diseases in PI. The greatest effect was observed in the prevention of skin infections and respiratory diseases of the upper respiratory tract as a reduction of respiratory episodes frequency, acceleration of recovery and lighter course of the disease. Also, the combination of probiotic and vitamin D has proven itself as a means of preventing hypovitaminosis D in PI.